Potential and Challenges of Ecotourism Development in West Sinjai District, Sinjai Regency - Musdalifah Musdalifah; Muhammad Amar (Lembaga Pengembangan Kinerja Dosen, 2024)
One of the great potentials in Terasa Village to become an ecotourism area is a culture that has its own characteristics, mutual cooperation that is still active, and has a tourist area of Laliako Waterfall. This area has attractiveness and uniqueness, such as biophysical potential and cultural potential. The beauty of the natural panorama, the diversity of flora, fauna and diverse ecosystems and the challenges of the terrain are often the main attraction, as well as the cultural diversity of the Terasa Village community. The government can further assist the development of ecotourism by providing both tangible (capital) and intangible (security, knowledge) support. This condition encourages local communities to manage their tourism potential. One of the developments is the Laliako Waterfall tourist attraction which can be an alternative to community visits on weekends, as well as local culture that is still well preserved as one of the cultural preservation by the Terasa Village community located in Pattiro Hamlet and Laha-laha Hamlet.